The Positive Impact of Internet-Based Resources to Encourage Students’ Vocabulary Aspect - Puspitasari, Ema; Wijaya, Toni (Tapis: Jurnal Penelitian Ilmiah, 2022)
Internet-Based Resources is one of the solutions for increasing an aspect of English proficiency. This study aimed at knowing the Internet-Based Resources in their learning and to encourage English students’ vocabulary. The method used in this research is experimental research. Sample of this study consisted of English students including 26 students as the experimental group and 26 students as the control group. Each class had five sessions that must be completed, those were treatments for three times, one post-test, and one pre-test. The result found that IBR is effective for students’ vocabulary in writing an interesting, exciting to use and in combining their ideas with new words or vocabulary easier. The mean of the post-test in the control group was 73.53, on the other hand, in the experimental group was 83.12; the degrees of freedom totaled 25, the sig. (2-tailed) was 0.000, and the standard deviation was 8.500. The computation shows that the t-test has a higher score. Thus, it can be concluded that there is a positive impact of this method to encourage students’ vocabulary in English Language Program. The vocabulary mostly achieved for pre-test and post- test in the control group was 412 to 370. However, in the experimental group, the pre-test and post-test ranged around 355 to 470. The increasing ratio of the experimental groups in acquiring vocabularies over Internet-Based Resources was 13.90%.